NILAI-NILAI EKONOMI RUMAH TANGGA DALAM MEMPENGARUHI KEPUTUSAN WANITA DI PERKOTAAN UNTUK MASUK PASAR KERJA DI SUMATERA SELATAN - Rosmiyati Chodijah (Department of Development Economics, Universitas Sriwijaya, 2008)
In approximating factors influencing decision for coming on the market activity there are some characteristic factor influencing it. The factors are wage (earnings), earnings of non labor income, individual characteristic, social environment characteristic, and household chartered investment counsel values. The variables have an effect on in signifikan to decision of individuals work in market activity. Existence of individual characteristic influencing number of hours working respondent from model equation of the regression, there are some characteristics variables having an effect in signifikan and have an effect not signifikan. At this research known that average of earnings of respondent is bigger than household chartered investment values so that, can be said that by woman working in urban in south Sumatera, work rationally element inexistence perforced. From estimation earnings yield is found empirically factors influencing decision for working, have some enough considerations for women having reasoning of higher educations for taking decision coming on the market activity. The side also, known that existence of trend of friction of decision making which seen from culture working woman, so that, can influence their productivity. Key Words: Decision of individuals work, Market activity, Economic Value.